Performance, emission and combustion characteristic assessment of biodiesels derived from beef bone marrow in a diesel generator - SAYIN, CENK (PERGAMON-ELSEVIER SCIENCE LTD, 2020)
This paper discusses the performance, exhaust emissions and combustion of a diesel generator fueled with two different biodiesels, and their blends. In the experiments, animal fat biodiesel (AFB) obtained from beef bone marrow, vegetable oil biodiesel (VOB) derived from safflower/canola oil mixture, and ultra-low-sulfur diesel (ULSD) were used as pure. In addition, 50% by volume of AFB was mixed with ULSD (AFB50), and 50% by volume of VOB was mixed with ULSD (VOB50). All engine tests were conducted at a constant engine speed of 1500 rpm for three different diesel generator loads (3.6, 7.2, and 10.8 kW). According to the results, when the AFB and its blend were used as fuel in a diesel generator, it was determined that cylinder gas pressure (CP) and net heat release rate (HRR) values were higher, and raised earlier in all loads compared with VOB and ULSD. Moreover, the values of mean gas temperature (MGT) and exhaust gas temperature (EGT) were increased with the use of AFB compared to other test fuels, whereas thermal efficiency (TE), carbon monoxide (CO) and hydro carbon (HC) emission decreased in general. The carbon dioxide (CO2) emission was also higher than ULSD, but remained lower than VOB. The nitrogen oxide (NOx) emission was found to show a similar change in all types of fuel. (C) 2020 Elsevier Ltd. All rights reserved.
Keywords: Animal fat biodiesel; Vegetable oil biodiesel; Ultra-low-sulfur diesel; Diesel generator load; Engine performance and combustion; Exhaust emissions; ANIMAL FAT BIODIESEL; FRYING PALM OIL; EXHAUST EMISSIONS; ENGINE PERFORMANCE; FUEL BLENDS; METHYL-ESTERS; INJECTION; TALLOW; BEHAVIOR; IMPACT